CHARACTER EDUCATION THROUGH PEER ASSESSMENT - I.G.A. Lokita Purnamika Utami (LPPM Universitas Negeri Yogyakarta, 2012)
Abstract: This paper is aimed at revealing an idea that some positive values that are similar to the traits of character education can be generated through peer assessment. Peer assessment is defined as an assessment which involves the process of reviewing, valuing and giving comments and suggestion toward their peer‘s work. This way the students subconsciously generate some positive values such as respectful, helping and understanding, confident (self-esteem), independent, persistent, and responsible. Therefore, peer assessment offers academic benefits such as personal accountability, as well as interpersonal and collaborative skills that not only help students academically but also socially as a member of society. Keywords: peer assessment, character education